Skin-window study on the migration of leukocytes of newborns and infants - Miler, I; Holub, M; Vondrácek, J; Jouja, V; Hromádková, L (Folia microbiologica, 1979)
Migration of leukocytes of newborns and of infants up to the age of 6 months was studied using the in vivo skin-window technique according to Rebuck. Using the non-specific stimulation (abrasion of the skin only) a slight age-dependent physiological increase of migration of cells was observed within the observation period; after a strong local irritation with diphtheria-tetanus-pertussis vaccine (Alditepera) there was a vigorous migratory response of cells in the skin lesion. Both quantitatively and qualitatively, the migration pattern (i.e. shift from PMN leukocyte to mononuclear cells in the exudate within a 1 d period after abrasion) was not influenced by immunization of infants with Alditepera, suggesting thus the nonspecific nature of this cellular response. The "normal" values of the chemotactic response of leukocytes of newborns and infants are given as a basis for evaluation of defects of this functional activity of leukocytes.
Keywords: imunizace; novorozenec; Infant, Newborn; Skin Window Technique; difterický toxoid; Infant; Humans; Diphtheria Toxoid; kojenec; Pertussis Vaccine; pertusová vakcína; věkové faktory; neutrofily; lidé; Tetanus Toxoid; Chemotaxis, Leukocyte; technika kožního okénka; Neutrophils; chemotaxe leukocytů; Age Factors; tetanový toxoid; Immunization